Decarbonising the Alberta power system with carbon pricing. (May 2016) - Lyseng, B.; Rowe, A.; Wild, P.; English, J.; Niet, T.; Pitt, L.
Abstract: The Alberta power system, like many systems in the world, faces a supply gap and pressure to reduce CO2 emissions. A techno-economic optimisation model of the Alberta power system is developed in the Open Source Energy Modelling System (OSeMOSYS) to explore the impact of carbon pricing to 2060. Costs, emissions, and generation mixes are compared for thirteen scenarios. Carbon pricing accelerates the decarbonisation process, although with decreasing effectiveness. The most cost-effective reductions come via the transition from coal to natural gas. Coal with CCS becomes economic in most scenarios, indicating that low-carbon baseload generation is valuable. Natural gas plants provide valuable dispatchable generation, whether or not extensive build-out of wind and solar power occurs. Highlights: Alberta's fossil fuel-based power system is modelled in OSeMOSYS. Thirteen scenarios with different carbon prices, costs, and loads are simulated. Coal to natural gas baseload shift provides most cost-effective emission reductions. 30/tCO2 is sufficient to meet IPCC 2 °C carbon intensity through to 2030. Dispatchable generation remains essential with extensive variable renewables.